2020
DOI: 10.1107/s2052252520003036
|View full text |Cite
|
Sign up to set email alerts
|

Strong hydrogen bonding in a dense hydrous magnesium silicate discovered by neutron Laue diffraction

Abstract: A large amount of hydrogen circulates inside the Earth, which affects the long-term evolution of the planet. The majority of this hydrogen is stored in deep Earth within the crystal structures of dense minerals that are thermodynamically stable at high pressures and temperatures. To understand the reason for their stability under such extreme conditions, the chemical bonding geometry and cation exchange mechanism for including hydrogen were analyzed in a representative structure of such minerals (i.e. phase E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The crystal was exposed to the neutron beam for ~2.5 days in total at a TOF Laue diffractometer TOPAZ installed at the Spallation Neutron Source (SNS), Oak Ridge National Laboratory, which was operated at 1.4 MW proton beam power (Schultz et al 2014). The crystal was cooled down to 100 K by cold nitrogen gas, where the signal-to-noise ratio of higher-order reflections was enhanced (Purevjav et al 2016(Purevjav et al , 2018(Purevjav et al , 2020. For covering the full reciprocal space, we sequentially reoriented the crystal to have 25 different orientations with the help of the CrystalPlan software (Zikovsky et al 2011).…”
Section: Neutron Diffraction and Major Element Distributionmentioning
confidence: 99%
“…The crystal was exposed to the neutron beam for ~2.5 days in total at a TOF Laue diffractometer TOPAZ installed at the Spallation Neutron Source (SNS), Oak Ridge National Laboratory, which was operated at 1.4 MW proton beam power (Schultz et al 2014). The crystal was cooled down to 100 K by cold nitrogen gas, where the signal-to-noise ratio of higher-order reflections was enhanced (Purevjav et al 2016(Purevjav et al , 2018(Purevjav et al , 2020. For covering the full reciprocal space, we sequentially reoriented the crystal to have 25 different orientations with the help of the CrystalPlan software (Zikovsky et al 2011).…”
Section: Neutron Diffraction and Major Element Distributionmentioning
confidence: 99%
“…Lawsonite (8 GPa) and phengite (6 GPa) are likely the hydrous minerals in the sedimentary and basaltic layers (Poli & Schmidt, 2002; Schmidt & Poli, 1998). In the peridotitic layers, these minerals may include antigorite (∼6 GPa) and dense hydrous magnesium silicates such as phase A (6–14 GPa), phase E (15 GPa), phase D (15–40 GPa), and 10 Å‐phase (6.7 GPa) (Ohtani, 2015; Ono, 1998; Purevjav et al., 2020; Tomioka et al., 2016). However, these hydrous minerals are thermodynamically unstable at relatively high temperatures, i.e., >1300–1400°C (Ohtani, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Phase E has trigonal symmetry and crystallizes in the rhombohedral space group Rtrue3¯m $R\bar{3}m$; its structure consist of brucite‐like octahedral layers with tilted O‐H dipoles that are cross‐linked by statistically distributed Si‐tetrahedra and Mg‐octahedra (Kudoh et al., 1993; Tomioka et al., 2016). It has a nonstoichiometric formula depending on the hydrogen content and composition, and the Mg‐endmember has a general chemical formula of Mg 3−0.5x Si x H 6−3x O 6 , where x varies between 1 and 1.3, with a H 2 O storage capacity of 11–18 wt% (Purevjav et al., 2020; Tomioka et al., 2016). Two previous X‐ray diffraction (XRD) studies reported an isothermal bulk modulus of K T 0 = ∼93 GPa and its pressure derivative of KT0 ${K}_{T0}^{\prime }$ = 5(1) for both iron‐free and iron‐bearing phase E (Crichton & Ross, 2000; Shieh et al., 2000).…”
Section: Introductionmentioning
confidence: 99%